THU0156 NO CONFIRMATION OF INCREASED RISK OF IDIOPATHIC FACIAL NERVE PALSY UNDER TOCILIZUMAB. (June 2019) - Strangfeld, Anja; Meißner, Yvette; Schaefer, Martin; Baganz, Lisa; Schneider, Matthias; Wilden, Elke; Zinke, Silke; Zink, Angela
Abstract : Background: Spontaneous reports of nine facial paralyses and five facial pareses made by healthcare professionals from Europe have recently prompted EMA's Pharmacovigilance Risk Assessment Committee (PRAC) to consider a potentially increased risk of idiopathic facial nerve palsy for patients receiving tocilizumab. Objectives: To assess whether this signal can be confirmed with data of a large data set with known denominators for various treatments, comparing the risk in patients receiving tocilizumab with the risk in patients receiving other DMARDs. Methods: The German register RABBIT is a prospective longitudinally followed cohort of RA patients with a new start of a DMARD after at least one csDMARD failure. For this analysis, patients were included who were enrolled with a biologic DMARD start between 01/2007 and 04/2018. DMARD specific, unadjusted incidence ratios were calculated. Results: Between 2007 and 2018, a total of 20 facial nerve palsies (FNP) were observed in 11963 RABBIT patients, of those, three were excluded due to obvious reasons (e.g. stroke) leaving 17 idiopathic FNP. Three of them were observed in tocilizumab patients, leading to an incidence rate of 0.47 per 1000 PY (95% CI: 0.10, 1.14), which is higher than the incidence rate observed in patients receiving conventional synthetic (cs)DMARDs (0.21, 95% CI: 0.04; 0.51) but does not stand out among the incidence rates observed for other biologicals (see Table 1 ). The overall incidence of an idiopathic FNP among patients receiving (synthetic or biological) DMARDs was 0.37 (95% CI: 0.22, 0.57) which is higher than the incidence of idiopathic FNP in the general population (with 20-30 cases per 100, 000 persons [1]). Age and gender were roughly equally distributed among patients with and without idiopathic FNP. Patients with idiopathic FNP had longer disease duration, more frequently presented with joint erosions and with prior treatment with biologics. They also had lower physical function and more comorbidities. In one patient with idiopathic FNP receiving treatment with Rituximab (original biologic) a Sjoegrens' syndrome was reported as comorbidity, which is associated with an increased risk of neuropathies. Conclusion: The overall incidence of idiopathic FNP among rheumatoid arthritis patients receiving DMARDs was higher than the incidence in the general population. However, an increased risk for patients receiving tocilizumab compared to patients treated with other biologicals cannot be confirmed. The incidence of idiopathic FNP is higher for patients receiving biologicals compared to patients receiving csDMARDs. This might be due to the higher disease activity. However, the small number of cases with an idiopathic facial nerve palsy is a limiting factor in analysing and interpreting these results. Reference: [1] Murthy, J.M.K., Saxena, A.B. (2011): Bell's palsy; treatment guidelines. Ann Indian Acad Neurol. 2011 Jul;14(Suppl1): S70–S72. * One patient was exposed to both Etanercept (original) and Rituximab at the time of event. Acknowledgement: Disclosure: RABBIT is supported by a joint, unconditional grant from AbbVie, Bristol-Myers Squibb, Celltrion, Hexal, Lilly, MSD Sharp & Dohme, Pfizer, Roche, Samsung Bioepis, Sanofi-Aventis and UCB Disclosure of Interests: Anja Strangfeld Speakers bureau: Speakers fees from Bristol-Myers Squibb, MSD, Pfizer, Roche, Yvette Meißner Speakers bureau: Pfizer, Martin Schaefer: None declared, Lisa Baganz: None declared, Matthias Schneider Grant/research support from: GlaxoSmithKline and UCB Pharma for performing the LuLa-study., Speakers bureau: Chugai, Elke Wilden: None declared, Silke Zinke: None declared, Angela Zink Speakers bureau: Speakers fees from AbbVie, Janssen, Pfizer, Roche, Sanofi